The Role of Self-Intention in Mediating the Influence of Teacher Competency and YouTube Media on Learning Outcomes in Elementary School - Vitri Adinda Ajining Putri; Rihab Wit Daryono; Annisa Dwi Kurniawati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Teachers create an intrinsic urge to continue to improve themselves and utilize YouTube media as a practical learning tool. On the other hand, students' self-intentions determine how actively they use YouTube media to deepen their understanding of arts and culture. This research explores the urgency and influence of teacher competence and YouTube media intensity on Arts and Culture learning outcomes through students' self-intentions. Method: The survey method was used to collect data based on probability sampling from 68 students at Elementary School 1 Surodikraman Ponorogo. Data collection was carried out using a questionnaire consisting of a Likert scale with four alternative answers. PLS-SEM analysis is used to analyze data and test and evaluate the construction of variables measuring problem-solving abilities. Results: The analysis shows that teacher competency on self-intention and self-intention on learning outcomes have an insignificant effect. Furthermore, self-intention was proven not to mediate teacher competency and YouTube media's influence on learning outcomes. Novelty: This study presents a novelty by showing that self-intention does not mediate these factors. This finding suggests that other factors may be more influential in mediating these effects, which could be investigated by future research. Recommendations for this research include training on teacher awareness and motivation in effectively using YouTube media.